Strategi Pendampingan Dan Akselerasi Pemahaman Instrumen Akreditasi Program Studi Bagi Sivitas Akademika Sebagai Upaya Penjaminan Mutu Berkelanjutan - Paulina Siregar; Ahmad Taufik; Endang Sri Kurniatun; Lindra Kristiana (PPM Sdirjianbang Akademi Militer, 2026)
The dynamics of higher education regulations in Indonesia, currently governed by Permendiktisaintek Number 39 of 2025, necessitate a shift in the accreditation system by emphasizing educational outcomes and achievements. However, limited understanding of the latest instruments and a lack of collaboration among the academic community remain primary obstacles in preparing the Self-Evaluation Report (LED). This community service initiative aims to accelerate the understanding of accreditation instruments using the Participatory Action Learning System (PALS) approach, which is divided into three stages: Socialization, Technical Guidance, Simulation and Evaluation. The results of the implementation showed a significant increase in participants' understanding, with average scores rising from 57 (pre-test) to 77 (post-test). Despite this progress, specific challenges were identified at the Military Academy, including the command system, personnel rotation (Tour of Duty), and the lack of an integrated digital management information system. This mentoring strategy proved effective in fostering a quality culture and collective responsibility, ensuring the sustainable quality of study programs